PENGARUH INTEGRASI MODEL PEMBELAJARAN SIKLUS 5E DENGAN CASE BASED LEARNING (CBL) TERHADAP KECENDERUNGAN BERFIKIR KRITIS MAHASISWA - Kusumawati, Wiwik; Kurniasari, Novita; Khusniyah, Zulfa (Universitas Pesantren Tinggi Darul Ulum, 2019)
ABSTRACT Critical thinking is an important competency to be developed during the nursing education process. Critical thinking is needed by nurses to make clinical decisions related to problems experienced by patients. However, several studies mention the tendency and critical thinking ability of nursing students is still low. One effort to overcome this is by applying learning methods that enable students to learn actively such as the 5E cycle learning method with CBL. The purpose of this study was to determine the effect of the integration of learning cycle 5E with CBL on students' thinking tendencies. The research design used was a Quasy experiment with a pre test post test with control group approach. The research sample was 21 students 5th semester of Nursing Unipdu Jombang as a treatment group and 19 students of Nursing study at the Health Development Program Mojokerto PPNI as a control group. Data analysis techniques used were paired t-test and Independent t-test. The results showed there were significant differences in the tendency of critical thinking both in the treatment group and the control group before and after the intervention was given with a value of p = 0.001 for the treatment group and p = 0.004 for the control group. There is a significant influence on the integration of the 5E cycle learning model with CBL on the tendency of critical thinking with a value of p = 0.043 (??0.05). Integration of the 5E cycle Learning model with CBL can increase the critical thinking tendency because it can activate the use of higher order thinking skills such as the ability to analyze, synthesize and draw conclusions. Thus the integration of the 5E and CBL cycle learning models can be used as an alternative learning method to increase students' critical thinking tendencies. Keywords : 5E Cycle Learning Model, Case Based Learning (CBL), Critical Thinking Trends